(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the relationship between motivation strategies and self-regulated learning, motivation strategies and academic performance, and self-regulated learning and academic performance. The study's respondents were the students in the selected schools in CARAGA Davao Oriental division. There were 5 schools selected in this study, each with 50 selected students to participate. Hence, a total of 250 students would participate through random sampling. The finding revealed that the extent of motivation strategies in terms of Intrinsic Motivation, Extrinsic Motivation, and Self-Efficacy in Learning suggests that motivation strategies were pervasive and interpreted as always manifested. The overall mean rating of 4.30 with the descriptive rating of very extensive denotes the pervasive motivation strategies of learners in Caraga Davao Oriental. The extent of self-regulation regarding Metacognition Strategies and environmental Structuring was moderately extensive, academic improvement was moderately extensive, and Computer Self-Efficacy was moderately extensive. The overall mean rating denoted moderately extensive self-regulation due to some factors, such as distraction or parental support of their learners. The Academic Performance of Students was very extensive. There was a significant relationship between motivation strategies and self-regulated learning. There was a significant relationship between the motivation strategies and academic performance. There was a substantial relationship between self-regulated learning and academic performance. The study highly recommended that Educators or teachers try to adopt student-centered classroom activities and encourage students to self-regulate their learning processes